Factors influencing behavioural intention for mobile banking adoption among students of Universiti Putra Malaysia - Osman, Syuhaily; Tan, Pik Leng (Malaysian Consumer and Family Economics Association, 2020)
Along with the increasing sophistication of the banking industry and the era of smartphones and tablets, banking services and technology are showing tremendous growth. However, the numerous benefits brought by the use of mobile banking do not indicate that the consumers will be eager to adopt the new mobile banking services offered in Malaysia. Therefore, the main purpose of this study was to determine the factors influencing the behavioural intention to adopt mobile banking among Universiti Putra Malaysia students. The data were collected from 200 respondents through a set of self-administered questionnaires, where descriptive analysis, Pearson’s correlation analysis, and multiple regression analysis were employed to analyse them. The findings then showed that performance expectancy, habit, and perceived credibility were significant predictors for behavioural intention among students, whereby performance expectancy was underlined as the most significant predictor. The findings of the study have thus offered several implications that would be beneficial to service developers, banks, and future researchers alike.